The influence of service quality and price on customer loyalty in e-commerce Shopee (case study on consumers using the Shopee application) / Yus Yus Rita … [et al.] - Rita, Yus Yus; Safrida, Safrida; Riana, Zenni; Nasution, Ismail (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The purpose of the study was to determine the effect of service quality and price on consumer loyalty who use the Shopee e-commerce application. The types of data used are primary and secondary data, where the secondary data can be found on the website or Shopee application itself and from some consumer comments on the application on various internet networks. This study used a sample of 86 respondents, with Non-Probability Sampling technique in the form of Ancidental Sampling. From the results of data processing using the help of SPSS software, the results showed that: Based on hypothesized data the quality of service (X-1) significantly affects consumer loyalty (Y), where X-1 obtained a calculated T value of 2.244 >1.663 and a significance value of 0.028